2018
DOI: 10.1007/s11999.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Risk Adjustment Is Necessary in Value-based Outcomes Models for Infected TKA

Abstract: Background The Medicare Access and CHIP Reauthorization Act of 2015 provides the framework to link reimbursement for providers based on outcome metrics. Concerns exist that the lack of risk adjustment for patients undergoing revision TKA for an infection may cause problems with access to care. Questions/purposes (1) After controlling for confounding variables, do patients undergoing revision TKA for infection have higher 30-day readmission, reoperation, and mortality rates than those undergoing revision TKA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Complications, Reoperations, and Readmissions THA revision for infection was associated with an increased risk of major complications and reoperation, which can substantially affect episode-of-care cost. These findings are consistent with previous research that showed infection was an independent risk factor associated with 30-day complication, readmission, reoperation, and mortality after revision TKA [6]. While greater numbers comorbidities may be associated with the development of PJI after primary THA [9,10], these comorbidities do not fully predict the extent of unfavorable outcomes after revision THA.…”
Section: Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…Complications, Reoperations, and Readmissions THA revision for infection was associated with an increased risk of major complications and reoperation, which can substantially affect episode-of-care cost. These findings are consistent with previous research that showed infection was an independent risk factor associated with 30-day complication, readmission, reoperation, and mortality after revision TKA [6]. While greater numbers comorbidities may be associated with the development of PJI after primary THA [9,10], these comorbidities do not fully predict the extent of unfavorable outcomes after revision THA.…”
Section: Limitationssupporting
confidence: 88%
“…Although a recent study has found that patients undergoing revision TKA for septic causes have more complication, more frequent hospital readmissions, and higher 30-day mortality rates than patients undergoing aseptic revision TKA [6], large studies directly comparing outcomes of patients undergoing infected and aseptic revision THA have been lacking. Jafari et al [14] found that for individuals undergoing revision THA, infection was most the common cause of revision failure.…”
Section: Rationalementioning
confidence: 99%
“…Notably, advanced age, some comorbidities, and use of government insurance have been reported as independent risk factors for increased resource utilization for total joint arthroplasty (TJA). 8 - 10 …”
Section: Introductionmentioning
confidence: 99%
“…In the current study [4], Courtney and colleagues describe their experience with including the traditionally high risk and high-cost infected revision knee in their institution's knee arthroplasty bundle payment plan [3,4]. Generally, patients with a variety of risk factors-high BMI, immunocompromise, or solid-organ failure-may not be offered arthroplasty surgery because they are correctly perceived to be at greater risk for serious complications, and surgeons and healthcare systems alike tend to shy away from the financial risks associated with their care.…”
mentioning
confidence: 73%
“…The authors of the current study identified patient comorbidities that result in increased financial risk should a bundled payment model be implemented for infected revision knee arthroplasty [4]. The authors searched the American College of Surgeons National Surgical Quality Improvement Program® (NSQIP) database and identified more than 10,000 revision knee arthroplasties conducted by orthopaedic surgeons in a wide range of geographic and practice settings.…”
mentioning
confidence: 99%